The Implementation of Just in Time Teaching (JiTT) Model Integrated with TPACK: Modernizing Islamic Education Learning Through Technology-Based Learning - Sastradika, Dedi; Rozal, Edi; Salahuddin, Salahuddin; Rasidin, Rasidin; Andriani, Reni; Mirnawati, Mirnawati (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
The implementation of technology-based learning at Junior High School (SMP) 7 Jambi city is a solution that can be offered in producing human resources who have a level of technological literacy integrated with Islamic knowledge to minimize the negative effects of current technology use. The purpose of this study is to implement TPACK-based learning as a solution in optimizing the use of technology at schools as a solution in achieving learning modernization. Quantitative methods with One-Group Pretest-Posttest designs were employed in this study to determine the achievement of student learning outcomes before and after learning. The results of the study showed that there was a significant difference between student learning achievement before and after where the t-test was 0.001 which means that learning proces through JiTT Model integrated with TPACK had a positive impact on student achievement. This study only focused on developing learning by integrating technology in the application of learning. Future research is expected to develop technology that is appropriate for learning at schools.